Functional analysis of carbon sequestration in an interandean dry tropical forest (2019)
Changes in functional traits related to carbon sequestration during secondary succession of Dry Tropical Forest (DTF) in Colombia are poorly understood. Here we analyze how carbon sequestration shifts along three successional stages: abandoned pastures, shrubs, and secondary forests, following a trait-based approach at both species and community level. We measured seven functional traits in 41 abundant woody species. We identified four plant functional types (PFTs) related to conservative and acquisitive strategies. Both basal area and relative abundance of acquisitive PFT decreased through successional stages. In contrast, the patterns of change for conservative PFT were less consistent. The Community-weighted mean (CWM) for specific leaf area, leaf dry matter content, wood density, and maximum height were significantly higher in secondary forests compared to early successional stages. These findings may help to broaden the understanding of carbon sequestration during DTF succession. © 2019, Universidad Nacional de Colombia. All rights reserved.